2014
DOI: 10.1103/physreve.90.012126
|View full text |Cite
|
Sign up to set email alerts
|

Code-division multiple-access multiuser demodulator by using quantum fluctuations

Abstract: We examine the average-case performance of a code-division multiple-access (CDMA) multiuser demodulator in which quantum fluctuations are utilized to demodulate the original message within the context of Bayesian inference. The quantum fluctuations are built into the system as a transverse field in the infinite-range Ising spin glass model. We evaluate the performance measurements by using statistical mechanics. We confirm that the CDMA multiuser modulator using quantum fluctuations achieve roughly the same pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…QAA-like protocols have also been successfully implemented in condensed matter systems [3]. While the quantum distribution obtained from the QAA will not generally be the thermal distribution one would find with zero transverse field, it has been demonstrated experimentally that a quantum annealer can be used for thermal sampling under some circumstances [10], it has also been demonstrated numerically that in some cases the transverse field can act as an effective proxy for finite temperature [11,12]. Recent work has also suggested that the dissipation from open quantum system effects in QA can lead to an improvement in performance over AQC [29].…”
Section: Quantum Annealing Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…QAA-like protocols have also been successfully implemented in condensed matter systems [3]. While the quantum distribution obtained from the QAA will not generally be the thermal distribution one would find with zero transverse field, it has been demonstrated experimentally that a quantum annealer can be used for thermal sampling under some circumstances [10], it has also been demonstrated numerically that in some cases the transverse field can act as an effective proxy for finite temperature [11,12]. Recent work has also suggested that the dissipation from open quantum system effects in QA can lead to an improvement in performance over AQC [29].…”
Section: Quantum Annealing Algorithmmentioning
confidence: 99%
“…It has been shown in [9] that for some machine learning tasks a quantum distribution at finite temperature is actually preferable to a Boltzmann distribution on a classical Ising model. For other tasks it has been shown that using quantum fluctuations as a proxy for thermal distributions is sub-optimal, but makes little difference in practice [11,12]. An approximate thermal sample can be obtained by first taking all of the data from the states output by algorithm 2 at a desired T eff (perhaps throwing the first few iterations away as warm up period), and then applying the metropolis rules at = T T eff to obtain a fair thermal sample within each of these local minima.…”
Section: Applications To Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, given prior information about the channel noise (and therefore about the likely distribution of the received set of couplers J′ ), maximum entropy inference can be used to obtain better decoding performance than the maximum likelihood approach. More recently the role of quantum fluctuations on inferential problems including decoding have been considered 15 16 17 . The current paper does not seek to determine the role of quantum fluctuations, in finding an optimal solution; instead it considers the extent to which thermal fluctuations (which will necessarily be present in any real implementation of a Sourlas decoder) may be exploited.…”
mentioning
confidence: 99%
“…The right panel shows Improvable regions (∆M > 0) in T -Γ (left) T0 = 1.0. Dashed lines indicate border at which ∆M = 0 holds for α = K/N = 2 (These were taken from ours[37]).…”
mentioning
confidence: 99%